Stimulus for Teacher's Reading Interest in Improving Teaching Performance and Competence - Norhayati (Universitas Serambi Mekkah, 2022)
This study aims to determine how efforts to increase interest in reading andteacher stimulus to competence. teaching at SD Negeri Rokan Hilir Riauteachers. The research subjects were all 8 teachers of the State ElementarySchool 004 Bukit Damar, Simpang Kanan District, Rokan Hilir Regency. Datacollection methods are observation techniques and interview techniques. Thedata processing technique uses a qualitative research approach and thepercentage formula. The results of the research show that the development ofthe program for organizing the love of reading educational reference books inthe library can improve the competence of teacher performance in teaching andlearning activities and teachers gain new experience in the implementation ofthe implementation of the learning implementation plan.